2021
DOI: 10.1007/s00402-021-04065-x
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative virtual reality distraction in TKA under spinal anesthesia: a preliminary study

Abstract: IntroductionThe effect of patient anxiety during the perioperative period has been shown to be of great importance in its influence on post-operative recovery. Over the last 10 years, virtual reality (VR) has been developed in anesthesia for patient's distraction by immersion. The aim of this study was to evaluate post-operative patient anxiety the day after TKA surgery under spinal anesthesia (SA) with or without VR distraction. Materials and methods A single-center, prospective cohort study was performed loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
0
2
1
1
Order By: Relevance
“…In the literature on VR interventions, Lahti et al (2020) reported that short‐term VR interventions are effective in reducing anxiety in patients undergoing surgery, while other studies have shown that VR interventions used in cardiology laboratories helped to reduce anxiety (Bruno et al, 2020; Morgen et al, 2021). In contrast to the findings of this study, Peuchot et al (2021) did not report a significant difference in postoperative anxiety scores in patients who underwent surgery, but they did observe a decrease in intraoperative adverse events. In terms of acupressure interventions, Aygin and Şen (2019) found that acupressure reduced the level of state anxiety in patients who underwent cardiac surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…In the literature on VR interventions, Lahti et al (2020) reported that short‐term VR interventions are effective in reducing anxiety in patients undergoing surgery, while other studies have shown that VR interventions used in cardiology laboratories helped to reduce anxiety (Bruno et al, 2020; Morgen et al, 2021). In contrast to the findings of this study, Peuchot et al (2021) did not report a significant difference in postoperative anxiety scores in patients who underwent surgery, but they did observe a decrease in intraoperative adverse events. In terms of acupressure interventions, Aygin and Şen (2019) found that acupressure reduced the level of state anxiety in patients who underwent cardiac surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…By reducing or in some cases eliminating the need for sedation, VR can lower the incidence of apnea [101]. In addition, studies of adults undergoing knee replacement have demonstrated improved intra-operative hemodynamics (reduced hypotension), decreased fentanyl requirement, and lower post-operative pain scores [102,103].…”
Section: Analgesic Potential Of Vr During Other Painful Medical Proce...mentioning
confidence: 99%
“…Immersive VR has also been exploited as a form of distraction therapy and adjunct to surgical anaesthesia to alleviate pain and anxiety and promote patient relaxation [ 106 , 107 , 108 ]. However, Peuchot et al reported that the use of VR for immersive distraction during total knee arthroplasty under spinal anaesthesia did not seem to reduce patient anxiety or alter patient satisfaction, although improvements in postoperative comfort and reductions in intraoperative complications were achieved [ 109 ]. In addition, as a rehabilitation tool, VR training, compared to sensory–motor training, was found to have a more favourable impact on pain, functional disability, and the modification of inflammatory biomarkers in post-traumatic osteoarthritis after an anterior cruciate ligament injury, although a negligible effect on bone morphogenic proteins expression was reported [ 110 ].…”
Section: Clinical Translation and Efficacy Of Orthopaedic Trauma Vr M...mentioning
confidence: 99%
“…Meanwhile, cost remains a prohibitive barrier for high-fidelity bone trauma VR systems, especially in resource-limited settings. Nevertheless, future VR tools are expected to be cheaper, more user-friendly, and in tandem with technological advancements [ 38 , 109 ].…”
Section: Drawbacks Of Vr In Bone Traumamentioning
confidence: 99%